Papillary Renal Cell Carcinoma Type 1 Accompanied by Hemorrhagic Anemia: A Case Report - Deddy Primadona Mulia; Zulkhair Ali; Novadian Suhaimi; Suprapti Slamet; Ian Effendi; Syahpri Putra Wangsa; Kgs. M. Yusuf Arief Akbar; Mediarty Syahrir; Fadil Pramudhya Hoesain; Ika Kartika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Kidney cancer or renal cell carcinoma (RCC) accounts for 5% and 3% of all adult malignancies in men and women, respectively, thus representing the 7th most common cancer in men, and the 10th most common cancer in women. The incidence of kidney cancer in the last two decades has shown an increase, but in recent years the death rate due to kidney cancer has decreased because it is increasing. Case Presentation: A 27 year old male patient came with complaints of bloody urination. Patients also complain of body weakness. Every time they are active, the weakness decreases if the patient rests. The patient was stated to be suffering from anemia and a left kidney tumor. There was bilateral antebrachial pitting edema. There was bilateral pretibial edema. Cytological examination revealed papillary renal cell carcinoma type 1. Conclusion: Papillary cell carcinoma type 1 is a kidney tumor that has a good prognosis, especially if found at an early stage. The classic symptoms of type 1 pRCC are anemia, hematuria and kidney swelling.